PROJECT HOURGLASS DAN REPRESENTASI MULTIDIMENSIONAL PERBATASAN ISRAEL-MESIR - Febryana, Dhannya (Multikultura, 2025)
The Israel–Egypt border functions not merely as a geographic demarcation, but as a social, political, and cultural space imbued with symbolic meaning. Since its establishment in 1906 up to the construction of Project Hourglass in 2010, this border has shifted from a colonial administrative line to a fragile symbol of peace and a site of global securitization. This study employs a qualitative approach based on literature review and representational analysis, drawing on Stuart Hall’s representation theory as well as David Newman and Anssi Paasi’s concepts of borders in area studies. The findings reveal that the Israel-Egypt border is represented through four main dimensions: security, economy, politics-diplomacy, and humanitarianism. Project Hourglass materializes these representations, reflecting the tension between safeguarding national security and reinforcing separation. This analysis concludes that the Israel-Egypt border is not merely a geographic fact, but a multidimensional socio-political construct produced through media discourse, political narratives, and public perception, thereby contributing to a deeper understanding of how border representations shape regional dynamics and influence international relations.